Low skeletal muscle mass and not systemic inflammation is associated with complications after free forearm flap reconstruction in oral cancer patients - Ansari, E; Carrillo Minulina, N; van Es, R J J; Dieleman, F J; Rosenberg, A J W P; Janssen, L M; Braunius, W W; Haitjema, S; van Cann, E M; de Bree, R (Elsevier Limited, 2025)
PURPOSE: To determine the prognostic value of systemic inflammatory indices and skeletal muscle mass (SMM) as factors for postoperative complications in patients with advanced stages of oral squamous cell carcinoma (OSCC) undergoing free forearm-flap (FFF) reconstruction. METHODS: In this retrospective cohort study of patients who underwent reconstruction of oral cavity defects with FFF after resection of oral cancer the SMM was assessed. Primary predictor variables inflammatory markers neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, lymphocyte-monocyte ratio, systemic immune inflammatory index and systemic inflammatory marker index, and skeletal muscle mass index were determined. Multivariate regression analyses were used to determine the associations between low SMM and/or systemic inflammatory indices and the occurrence of postoperative complications. RESULTS: The sample was composed of 131 patients. Low SMM was associated with any postoperative complications (OR 4.78, 95 % CI 1.73-13.17, p = 0.00). It was also associated with medical and surgical postoperative complications. Inflammatory indices were not found to be significantly associated with postoperative complications. The addition of elevated systemic inflammation to low SMM did not alter its predictive outcome. CONCLUSIONS: Low SMM in patients with OSCC is associated with the occurrence of postoperative complications after FFF reconstruction surgery. Inflammatory indices as measures of systemic inflammation were not found to be associated with an increased incidence of postoperative complications in these patients.
Keywords: Free flaps; Postoperative complications; Sarcopenia; Skeletal muscle mass; Surgical outcomes; Systemic inflammation; Oral Surgery; Oncology; Cancer Research; Journal Article